ANALYSIS OF UNDERSTANDING MATHEMATICS CONCEPTS ON NUMERATION ABILITY OF PRIMARY STUDENTS - Ernawati, Herni; Rigianti, Henry Aditia (PROGRES PENDIDIKAN, 2024)
Numeracy abilities and understanding mathematical concepts are interrelated. Numeracy abilities can increase if students understand mathematical concepts. Oleh karenaTherefore, the aim of these findings is to examine the relationship between understanding mathematical concepts and the numeracy abilities of elementary school students. Numerical skills have an important role in helping students understand mathematical concepts and apply them in real life situations, while a good understanding of mathematical concepts can help improve students' numeracy skills. For this topic, literature was selected through a screening process based on journal criteria published within the last five years. Data collection in this research involves analyzing data obtained from journals relevant to the research topic. Thus, the results of this research show that numeracy skills and understanding mathematical concepts influence each other and are important to develop further together.